The Role of the Intelkam Unit in Making Integrity Zone in SKCK Services Polres Metro Bekasi Kota - Arif Budianto (Indonesian Journal of Police Studies, 2021)
The high demands of the community for the realization of a bureaucracy that is transparent, accountable, free from corruption, collusion and nepotism (KKN) have resulted in bureaucratic reform is something that must be done by Government agencies. In effort prevention and eradication corruption, President Republic Indonesia (through Inpres Number 17 Year 2011) instruct to the Minister and Head Institution Country and Head Area for take steps that required corresponding Duty, function, and authority each in order prevention and eradication corruption Year 2012, with refer on Priority Development National in Plan Development Period Intermediate National Year 2010-2014 and Plan Work Government Year 2012. This study aims to determine how the efforts to realize and the factors that hinder the Bekasi City Metro Police Satintelkam in realizing the Integrity Zone through public services of the Bekasi City Metro Police SKCK. This research uses George Terry's POAC Management Theory and the concept of Efforts to analyze the research results. Approach that done researchers is approach qualitative. In doing research, researchers use method descriptive analysis. Research this have focus that is How an overview Implementation SKCK for manifest service prime (service excellent) by unit Intelligence Police Metro Bekasi City. Data obtained from interviews, observations, and document review. The validity of the data through the triangulation method. Data were analyzed through data reduction, data presentation, and then drawing conclusions. The results showed that the effort to realize the integrity Zone was successful at Polres Metro Bekasi City in terms of implementation, organization, supervision and control. However, it is necessary to add public services to eliminate inhibiting factors such as making more public service places so that public interest does not increase and accumulate at a certain point.